A 200 W broadband high power amplifier using hybrid power combining network and digital level control. Issue 5 (21st January 2020) - Alekajbaf, Yasin; Masoumi, Nasser; Mohammad‐Taheri, Mahmoud; Safavi‐Naeini, Safieddin
Abstract: In this article, a 2 to 6 GHz solid‐state power amplifier with 53 dBm output power has been analyzed, designed, and fabricated. To achieve a wideband high output power, we introduce a 16‐way hybrid power combiner based on microstrip planar binary and parallel structures. The simulation and measurement results of the proposed hybrid power combining network (PCN) show that the maximum power combining efficiency is around 86% with the insertion loss of around 0.6 to 1.5 dB and an isolation of 20 dB between the ports. Also, to compensate the output power variations due to the thermal and operating frequency changes across the bandwidth, a digital level control (DLC) unit utilizing an agile control algorithm is proposed which decreases the output power variations to 2% of the desired output power. A cooling heatsink fan system has been also designed in order to transfer the heat generated power to the air. The measured output power for the applied input continuous wave is higher than 52.5 dBm. In addition, the power added efficiency (PAE) is better than 15% across the wide portion of the bandwidth and the measured third‐order intermodulation is about 20 dBc (average).